Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/1346-8138.13644
|View full text |Cite
|
Sign up to set email alerts
|

One‐year safety and efficacy study of bilastine treatment in Japanese patients with chronic spontaneous urticaria or pruritus associated with skin diseases

Abstract: A number of second‐generation non‐sedating antihistamines are used in clinical practices over the world. However, long‐term safety and efficacy have not been proved high level evidence based medicine. We have performed an open‐label, multicenter, phase III study to evaluate the long‐term safety and efficacy of bilastine, a novel non‐sedating H1‐antihistamine for patients with chronic spontaneous urticaria (CSU) or pruritus associated with skin diseases (trial registration no. JapicCTI‐142528). Patients aged 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…The number and total duration of pruritus in each mouse was recorded within 30 min of the 1 mL dextran injections through the tail vein. The CAU mouse model was considered to be successfully established if the number and total duration of pruritus were significantly higher than the normal mice (Yagami et al, 2017 ). A total of 60 mice were successfully established as CAU models which were classified into: the blank group (model mice without any treatment), the negative control group (NC) (model mice transfected with empty vector plasmid), the OSMR-siRNA group (model mice transfected with OSMR-siRNA plasmid), the anti-phospho-STAT3 (Tyr705) + OSMR-siRNA group (model mice transfected with OSMR-siRNA plasmid + the JAK/STAT3 signaling pathway agonist), and the Tyr705 group (model mice treated with the JAK/STAT3 signaling pathway agonist) groups.…”
Section: Methodsmentioning
confidence: 99%
“…The number and total duration of pruritus in each mouse was recorded within 30 min of the 1 mL dextran injections through the tail vein. The CAU mouse model was considered to be successfully established if the number and total duration of pruritus were significantly higher than the normal mice (Yagami et al, 2017 ). A total of 60 mice were successfully established as CAU models which were classified into: the blank group (model mice without any treatment), the negative control group (NC) (model mice transfected with empty vector plasmid), the OSMR-siRNA group (model mice transfected with OSMR-siRNA plasmid), the anti-phospho-STAT3 (Tyr705) + OSMR-siRNA group (model mice transfected with OSMR-siRNA plasmid + the JAK/STAT3 signaling pathway agonist), and the Tyr705 group (model mice treated with the JAK/STAT3 signaling pathway agonist) groups.…”
Section: Methodsmentioning
confidence: 99%
“…Dear Editor, Bilastine, a nonsedating second-generation H 1 -antihistamine, has been widely utilized for urticaria in Japan based on the high-quality evidence provided by the excellent studies. 1,2 A previous randomized trial for perennial allergic rhinitis revealed bilastine is more effective than fexofenadine, 3 speculating its therapeutic potential for chronic spontaneous urticaria refractory to other antihistamines including fexofenadine.…”
Section: Effect Of Bilastine On Chronic Spontaneous Urticaria Refractmentioning
confidence: 99%
“…In a further long‐term study, 122 Japanese patients with CSU were treated with 20‐mg bilastine daily for 52 weeks . Total symptom score was significantly ( P < 0.001) improved by 2 weeks and remained the same thereafter.…”
Section: Bilastine In Urticariamentioning
confidence: 99%